(untitled) (INFERENCE: Journal of English Language Teaching, 2026)
Speaking anxiety often becomes a major challenge for EFL students, leading to low willingness or confidence when speaking in English. Cooperative learning techniques have been suggested to address this issue. This study aims to investigate EFL students’ perceptions of Numbered Head Together on their speaking anxiety. This study uses a descriptive qualitative method, with 58 students from a senior high school in Semarang. The data were gathered through a structured questionnaire using a five-point Likert scale and a semi-structured interview. The questionnaire data were analyzed descriptively to identify the response pattern, while the interview data were analyzed thematically. The findings indicate that students generally perceive NHT positively in reducing their speaking anxiety. The integration of the questionnaire and the interview findings shows that NHT creates a supportive learning environment, reduces the fear of negative evaluation, and fosters self-confidence in speaking activities.